الإسهام النسبي لفاعلية الذات في التنبؤ بأسلوب حل المشكلات لدى طلبة معهد الفنون الجميلة - كاظم لعيبي, فاتن (Journal of College of Education, 2021)
The search aims to identify :Self-efficacy level for the Institute of Fine Arts students .Distinguished methods among students of the Fine Arts Institute in solving problemThe relationship between self-efficacy and problem-solving methods for students of the Institute of Fine Arts .The relative contribution of self-efficacy to forecasting problem-solving method among among students of the Institute of Fine Arts .    The sample consisted of (400) male and female students , who were chosen according to the stratified random method by (203) males and (197) females from the six sections , according to the five classes , As the number of students who appeared in the sample from the first grade (88) , the second grade (68), and the third grade like them , and the fourth grade (80) , and the fifth grade (96) .    The following results were reached : The students of the institute use the goal-oriented method in a large way , and they use the creative method in a noticeable way, just as they do not use the confidence method in solving problems, while they  use the approach style in a large way, just as the students of the institute do not use the methods of personal control and Avoidance style .   Students of the Institute of Fine Arts enjoy an average level of self-efficacy  and students of the Institute of Fine Arts enjoy high self-regulation , self-confidence , and a low level of preference for difficult tasks , And the presence of a statistically significant correlation between the problem solving method (goal orientation , creative style, confidence in problem solving , the approach style) and the dimensions of self-efficacy and the overall score , There is no significant correlation between my style (personal adjustment , style Avoidance) and dimensions of self-efficacy and overall score, Contribution of self-efficacy in predicting the four problem solving methods (goal orientation, creative style , confidence in solving problem , and Approach style) .